Assessment of peritoneal metastases with DW-MRI, CT, and FDG PET/CT before cytoreductive surgery for advanced stage epithelial ovarian cancer. Issue 8 (August 2021) - Mikkelsen, Mette Schou; Petersen, Lone Kjeld; Blaakaer, Jan; Marinovskij, Edvard; Rosenkilde, Mona; Andersen, Gratien; Bouchelouche, Kirsten; Iversen, Lene Hjerrild
Abstract: Background: Preoperative assessment of peritoneal metastases is an important factor for treatment planning and selection of candidates for cytoreductive surgery (CRS) in primary advanced stage (FIGO stages III–IV) epithelial ovarian cancer (EOC). The primary aim was to evaluate the efficacy of DW-MRI, CT, and FDG PET/CT used for preoperative assessment of peritoneal cancer index (PCI). Material and methods: In this prospective observational cohort study, 50 advanced stage EOC patients were examined with DW-MRI and FDG PET/CT with contrast enhanced CT as part of the diagnostic program. All patients were deemed amenable for upfront CRS. Imaging PCI was determined for DW-MRI, CT, and FDG PET/CT by separate readers blinded to the surgical findings. The primary outcome was agreement between the imaging PCI and PCI determined at surgical exploration (the reference standard) evaluated with Bland-Altman statistics. Results: The median surgical PCI was 18 (range: 3–32). For all three imaging modalities, the imaging PCI most often underestimated the surgical PCI. The mean differences between the surgical PCI and the imaging PCI were 4.2 (95% CI: 2.6–5.8) for CT, 4.4 (95% CI: 2.9–5.8) for DW-MRI, and 5.3 (95% CI: 3.6–7.0) for FDG PET/CT, and no overall statistically significant differences were found between the imaging modalities (DW-MRI – CT, p = 0.83; DW-MRI – FDG PET/CT, p = 0.24; CT – FDG PET/CT, p = 0.06). Conclusion: Neither DW-MRI nor CT nor FDG PET/CT was superior in preoperative assessment of the surgical PCI in patients scheduled for upfront CRS for advanced stage EOC. Highlights: Imaging evaluation of peritoneal metastasis in epithelial ovarian cancer is challenging. The imaging peritoneal cancer index is underestimated compared to the surgical peritoneal cancer index. Neither DW-MRI nor CT nor FDG PET/CT is superior in assessment of the surgical peritoneal cancer index.